Case Report: Renal embolism and acute lower extremity arterial embolism complicated by acute compartment syndrome caused by the detachment of the main body of cardiac myxoma in a child - Jianbo Xue; Yi Hong; Xiaoyi Xu; Yiming Ni (Frontiers in Surgery)
BackgroundPrimary cardiac myxoma in pediatric patients is a rare disease, with an annual incidence of approximately 0.1–0.2 cases per million children. This report presents the case of an 11-year-old male who developed multiple peripheral emboli following the detachment of a left atrial myxoma. The patient presented to the emergency department with acute abdominal pain and sudden-onset pain and sensory loss in both legs. Physical examination indicated bilateral lower limb ischemia, which was corroborated by Doppler arterial ultrasound, revealing emboli in the abdominal aorta and bilateral common iliac arteries. Abdominal CT demonstrated patchy non-enhancing low-density areas in both kidneys and the spleen, while echocardiography identified a left atrial mass. A diagnosis of acute lower limb arterial embolism, renal embolism, and splenic embolism secondary to left atrial myxoma was established. Additionally, lower limb ischemia resulted in acute compartment syndrome. The multidisciplinary team initiated systemic anticoagulation, followed by abdominal aortic embolectomy, fasciotomy decompression, and left atrial myxoma resection. Postoperative outcomes were favorable, with no residual tumor in the left atrium and complete restoration of arterial perfusion in both lower limbs. Histopathological analysis confirmed the diagnosis of myxoma.ConclusionAlthough pediatric cardiac myxoma is exceedingly rare, the clinical presentation of peripheral embolism in this case raised a strong suspicion of an embolic etiology, facilitating rapid assessment and timely intervention.